Glazed ceramic tile and preparation method thereof

By using a combination of base glaze and surface glaze layers with different viscosity and surface tension on ceramic tiles, the problems of unclear edges of dry grain patterns and cumbersome processes in the prior art are solved, and the three-dimensional texture decorative effect of ceramic tiles is improved and Simplified process.

CN119462107APending Publication Date: 2025-02-18CHONGQING WONDERFUL CERAMICS CO LTD +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202411615815.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-18

Smart Images

  • Figure CN119462107A_ABST
    Figure CN119462107A_ABST
Patent Text Reader

Abstract

The invention provides a glazed ceramic tile and a preparation method thereof. The glazed ceramic tile comprises a ceramic body, a ground glaze layer arranged on the ceramic body and a cover glaze layer arranged on the ground glaze layer, the viscosity of the ground glaze layer is greater than that of the cover glaze layer, and the surface tension of the ground glaze layer is greater than that of the cover glaze layer. The viscosity and surface tension of the cover glaze layer are small, flowing glaze is easily formed, and an uneven glaze surface is formed after cooling, that is, the cover glaze layer generates a flowing glaze effect on the ground glaze layer, unique macroscopic ordered and microcosmic disordered three-dimensional textures are formed, the decoration effect is improved, glue patterns do not need to be printed, the problem that the edges of the patterns are not clear does not occur, and the service life of the product is prolonged. The process is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramic production, and in particular to a glazed ceramic tile and a preparation method thereof. Background Art

[0002] With the upgrading of the quality of ceramic tiles, it is not only reflected in the surface decoration, but also should be given more functions. Ceramic tiles with three-dimensional decorative effects are deeply loved by people. In order to make the brick surface effect of ceramic tiles richer, the ceramic industry has begun to use dry particles to decorate ceramic tiles. In the method of using dry particles to decorate ceramic tiles, it is usually to apply a base glaze on the surface of an ordinary body, then use glue to print a glue pattern, and then apply dry particles on the surface of the glue pattern, and finally apply a protective glaze to obtain a ceramic tile with a dry particle decorative pattern. Although the three-dimensional effect of the ceramic tiles obtained by this method is improved compared to conventional ceramic tiles, due to the direct application of dry particles on the glue pattern, the edge of the dry particle pattern is prone to unclear problems, and the process is cumbersome, and the three-dimensional decorative effect of the brick surface is not good.

[0003] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention

[0004] The technical problem to be solved by the present invention is that, in view of the above-mentioned defects of the prior art, a glazed ceramic tile and a preparation method thereof are provided, aiming to solve the problems in the prior art of decorating ceramic tiles with dry particles, such as unclear edges of dry particle patterns, complicated processes and poor three-dimensional decorative effects on the brick surface.

[0005] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0006] The first aspect of the present application provides a glazed ceramic tile, wherein the glazed ceramic tile includes: a ceramic body, a bottom glaze layer arranged on the ceramic body, and a surface glaze layer arranged on the bottom glaze layer; the viscosity of the bottom glaze layer is greater than the viscosity of the surface glaze layer, and the surface tension of the bottom glaze layer is greater than the surface tension of the surface glaze layer.

[0007] According to the above technical means, the viscosity of the surface glaze layer of the embodiment of the present application is relatively low. Glazes with low viscosity and surface tension have high fluidity at high temperatures, which can easily cause glaze flow. When the surface tension of the glaze is also very small, it is easier to form glaze flow, and after cooling, an uneven glaze surface is formed. In this way, the surface glaze layer of the embodiment of the present application produces a glaze flow effect on the bottom glaze layer, forming a unique macroscopically ordered and microscopically disordered three-dimensional texture, which enhances the decorative effect, and does not require printing of glue patterns, does not cause unclear pattern edges, and has a simple process.

[0008] In one embodiment of the present application, the base glaze layer is a titanium opacified glaze layer, and the surface glaze layer is a glossy glaze layer.

[0009] According to the above technical means, the bottom glaze of the embodiment of the present application uses titanium opacified glaze, which has a high silicon oxide content, a low potassium oxide and sodium oxide content, and a high viscosity and surface tension at high temperatures; the top glaze is a glossy glaze, which has a bright and smooth glaze surface and low viscosity and surface tension. In this way, the viscosity and surface tension of the titanium opacified glaze layer are high, and the viscosity and surface tension of the glossy glaze layer are low. The glossy glaze layer produces a glaze flow effect on the titanium opacified glaze layer, thereby forming a unique macroscopically ordered and microscopically disordered three-dimensional texture, which has a good decorative effect.

[0010] In one embodiment of the present application, the raw material formula of the base glaze layer includes, by mass percentage:

[0011] 8-12% kaolin, 22-30% high-temperature potassium sand, 20-26% quartz, 1-5% calcined talc, and 34-42% first frit.

[0012] According to the above technical means, the base glaze of the embodiment of the present application does not need to use zirconium silicate, thereby solving the problem of high cost caused by using zirconium silicate base glaze.

[0013] In one embodiment of the present application, the chemical composition of the first frit, measured by mass percentage, includes:

[0014] SiO2 54.97%, Al2O3 11.21%, Fe2O3 0.12%, CaO 13.75%, MgO 0.45%, K2O2.44%, Na2O 1.37%, ZnO 2.17%, TiO2 13.52% 。

[0015] According to the above-mentioned technical means, the chemical composition of the first frit in the embodiment of the present application has significant benefits in optimizing glaze performance, promoting glaze melting and reaction, and improving the quality of ceramic tiles. It can ensure that the glazed ceramic tiles form a uniform, smooth and decorative glaze during the firing process, while improving the durability and service life of the product.

[0016] In one embodiment of the present application, the chemical composition of the base glaze layer, measured by mass percentage, includes:

[0017] SiO2 70~74%, Al2O3 10~12%, Fe2O3 0.1~0.2%, CaO 5~6%, MgO 0.5~2%, K2O 1.5~2.5%, Na2O 1~2%, TiO2 5~6%, ZnO 0.5~1%.

[0018] According to the above technical means, the bottom glaze layer of the embodiment of the present application contains titanium dioxide, which undergoes photocatalytic action under light, accelerates the decomposition of dirt and bacteria, degrades pollutants, and inhibits bacterial reproduction.

[0019] In one embodiment of the present application, the raw material formula of the glaze layer includes, by mass percentage:

[0020] 20-30% albite, 8-12% calcite, 32-42% second melt, 8-12% quartz, 6-10% dolomite, 8-12% barium carbonate, 0.1-1% copper oxide, and 0-0.1% cobalt oxide.

[0021] According to the above technical means, the ratio of the glaze raw materials in the embodiment of the present application makes the glaze layer have suitable viscosity and surface tension, so as to produce an ideal glaze flow effect.

[0022] In one embodiment of the present application, the chemical composition of the second frit, measured by mass percentage, includes:

[0023] SiO2 52.37%, Al2O3 17.12%, Fe2O3 0.09%, CaO 11.42%, MgO 1.34%, K2O4.08%, Na2O 11.25%, BaO 1.96%, ZnO 0.37%.

[0024] According to the above-mentioned technical means, the chemical composition of the second frit in the embodiment of the present application has significant benefits in optimizing glaze performance, promoting glaze melting and reaction, and improving the quality of ceramic tiles. It can ensure that the glazed ceramic tiles form a uniform, smooth and decorative glaze during the firing process, while improving the durability and service life of the product.

[0025] In one embodiment of the present application, the chemical composition of the glaze layer, measured by mass percentage, includes:

[0026] SiO2 50~56%, Al2O3 10~12%, Fe2O3 0.05~0.1%, CaO 12~16%, MgO2~3%, K2O 1~2%, Na2O 6~8%, BaO 9~11%, ZnO 0.1~0.2%, CuO 0.1~1%, CoO 0~0.1%.

[0027] According to the above-mentioned technical means, the chemical composition of the glaze layer in the embodiment of the present application has significant benefits in optimizing physical properties, enhancing chemical stability, improving glaze decorative effects, and promoting glaze melting and reaction. It can ensure that the ceramic tiles form a high-quality, highly decorative glaze during the firing process, while improving the durability and service life of the product.

[0028] In one embodiment of the present application, the chemical composition of the ceramic body, measured by mass percentage, includes:

[0029] SiO2 70~72%, Al2O3 18~20%, Fe2O3 1.5~2.5%, CaO 1~1.5%, MgO1.0~2.0%, K2O 2~3%, Na2O 1~2%, TiO2 0.5~1.0%, others 0.5~1.0%.

[0030] According to the above technical means, the chemical composition of the ceramic body of the embodiment of the present application optimizes the physical properties of the ceramic tile, enhances the chemical stability, and improves the color and gloss.

[0031] A second aspect of the present application provides a method for preparing the glazed ceramic tile as described above, wherein the method comprises:

[0032] The ingredients are prepared according to a predetermined blank formula, and ball-milled to obtain a slurry;

[0033] The slurry is spray-dried to obtain ceramic powder, and the ceramic powder is pressed into a ceramic body;

[0034] After the ceramic body is dried, a pre-prepared base glaze is applied on the dried ceramic body to obtain a base glaze layer, wherein the base glaze has a glaze amount of 400 to 600 g / m 2 ;

[0035] Applying the pre-prepared top glaze on the base glaze layer to obtain a top glaze layer, wherein the amount of the top glaze applied is 700-1000 g / m 2 ;

[0036] The ceramic body with the bottom glaze and the top glaze applied is dried and then fired to obtain a glazed ceramic tile.

[0037] According to the above technical means, the amount of glazing applied to the bottom glaze in the embodiment of the present application is less than the amount of glazing applied to the surface glaze. Since the viscosity of the surface glaze layer is relatively small and the surface tension is also small, it has greater fluidity at high temperatures and is easy to form a flowing glaze. The amount of glazing applied to the surface glaze is relatively large, so that the surface glaze can form a more complex and rich flowing glaze texture. The surface glaze can be freely covered on the bottom glaze to form a unique macro-ordered and micro-disordered three-dimensional texture. The amount of glazing applied to the bottom glaze is relatively small. Since the main function of the bottom glaze layer is to adhere to the ceramic body and provide a smooth and uniform base for the surface glaze layer, the thinner bottom glaze layer can reduce the amount of glaze used and reduce costs without affecting its function as a base.

[0038] Beneficial effects of this application:

[0039] (1) The viscosity and surface tension of the titanium opalescent glaze layer in the embodiment of the present application are large, while the viscosity and surface tension of the glossy glaze layer are small. The glossy glaze layer produces a glaze flow effect on the titanium opalescent glaze layer, thereby forming a unique macroscopically ordered and microscopically disordered three-dimensional texture, which has a good decorative effect.

[0040] (2) The base glaze layer of the embodiment of the present application contains titanium dioxide, which undergoes photocatalytic action under light, accelerating the decomposition of dirt and bacteria, degrading pollutants and inhibiting bacterial reproduction.

[0041] (3) The amount of bottom glaze applied in the embodiment of the present application is less than that of the surface glaze. Since the surface glaze layer has a lower viscosity and a lower surface tension, it has greater fluidity at high temperatures and is prone to forming a flowing glaze. The amount of bottom glaze applied is smaller, which can reduce the amount of glaze used and reduce costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 It is a structural schematic diagram of a glazed ceramic tile in the present invention.

[0043] Figure 2 The present invention discloses a brick surface effect diagram of a glazed ceramic tile.

[0044] Figure 3 It is another brick surface effect diagram of a glazed ceramic tile in the present invention. DETAILED DESCRIPTION

[0045] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0046] like Figure 1 As shown, an embodiment of the present application provides a glazed ceramic tile, which includes: a ceramic body 100, a bottom glaze layer 200 arranged on the ceramic body 100, and a surface glaze layer 300 arranged on the bottom glaze layer 200; the viscosity of the bottom glaze layer 200 is greater than the viscosity of the surface glaze layer 300, and the surface tension of the bottom glaze layer 200 is greater than the surface tension of the surface glaze layer 300.

[0047] Specifically, the thickness of the bottom glaze layer 200 is less than that of the surface glaze layer 300, that is, the bottom glaze layer 200 is thinner and the surface glaze layer 300 is thicker. Since the surface glaze layer 300 has a lower viscosity and a lower surface tension, it has greater fluidity at high temperatures and is easy to form a flowing glaze. The surface glaze layer 300 is thicker and can form a more complex and rich flowing glaze texture. The surface glaze can be freely covered on the bottom glaze to form a unique macroscopically ordered and microscopically disordered three-dimensional texture. The bottom glaze layer 200 is thinner. Since the main function of the bottom glaze layer 200 is to adhere to the ceramic body 100 and provide a flat and uniform base for the surface glaze layer 300, the thinner bottom glaze layer 200 can reduce the amount of glaze used and reduce costs without affecting its function as a base. A thicker surface glaze layer 300 can provide better wear resistance, corrosion resistance and pollution resistance, and protect the ceramic body 100 from erosion by the external environment; at the same time, a thicker surface glaze layer 300 can also better show the glaze flow effect and enhance the decorativeness of the ceramic tile.

[0048] The surface glaze layer 300 of the embodiment of the present application has a relatively low viscosity. Glazes with low viscosity and surface tension have high fluidity at high temperatures, which can easily cause glaze flow. When the surface tension of the glaze is also very low, it is more likely to form glaze flow, and after cooling, an uneven glaze surface is formed. In this way, the surface glaze layer 300 of the embodiment of the present application produces a glaze flow effect on the bottom glaze layer 200, forming a unique macroscopically ordered and microscopically disordered three-dimensional texture, which enhances the decorative effect, and does not require printing of glue patterns, does not cause unclear pattern edges, and has a simple process.

[0049] In one embodiment of the present application, the base glaze layer 200 is a titanium opacified glaze layer, and the top glaze layer 300 is a glossy glaze layer.

[0050] Specifically, the bottom glaze of the embodiment of the present application uses titanium opacified glaze, which has a high silicon oxide content, a low potassium oxide and sodium oxide content, and a high viscosity and surface tension at high temperatures. The top glaze of the embodiment of the present application is a glossy glaze, with a bright and smooth glaze surface, and a silicon-aluminum molar ratio of 8 to 10. At the same time, the sodium oxide and barium oxide content are increased to reduce the high temperature viscosity and surface tension. In this way, the viscosity and surface tension of the titanium opacified glaze layer are large, and the viscosity and surface tension of the glossy glaze layer are small. The glossy glaze layer produces a glaze flow effect on the titanium opacified glaze layer, thereby forming a unique macroscopically ordered and microscopically disordered three-dimensional texture, which has a good decorative effect.

[0051] In addition, the embodiment of the present application combines the titanium opacifying glaze layer and the glossy glaze layer, which has the following effects:

[0052] First, the titanium opacified glaze layer usually has an opacifying effect, which can scatter light and reduce direct light penetration, thus giving the ceramic tile a soft and warm texture; the glossy glaze layer has high reflectivity and can enhance the glossiness of the ceramic tile surface. The combination of the titanium opacified glaze layer and the glossy glaze layer can form a unique macroscopically ordered (such as the overall gloss and color distribution) and microscopically disordered (such as the distribution of tiny particles in the opacified glaze layer and the flowing texture of the glossy glaze layer) three-dimensional texture. This texture is both regular and varied, which enhances the decorative effect of the ceramic tile.

[0053] Second, due to its opacifying properties, the titanium opacified glaze layer can increase the thickness and uniformity of the glaze surface, thereby improving the glaze's anti-wear, anti-corrosion and other properties.

[0054] Third, the combination of titanium opacified glaze layer and glossy glaze layer does not require additional steps for printing glue patterns, simplifying the production process. This application relies on the natural flow and cooling and solidification process of the glaze to form the texture, reducing the need for manual intervention and complex pattern design.

[0055] In one embodiment of the present application, the raw material formula of the base glaze layer 200 includes, by mass percentage:

[0056] 8-12% kaolin, 22-30% high-temperature potassium sand, 20-26% quartz, 1-5% calcined talc, and 34-42% first frit.

[0057] Specifically, when preparing the base glaze, the raw materials are mixed according to the above formula, and 0.1% sodium carboxymethyl cellulose (CMC), 0.05% sodium tripolyphosphate, 0.2% sodium hexametaphosphate, and 0.05% preservative (such as JS-3036, LF-15, JS-459, etc.) of the total mass of the base glaze are added, and the mixture is mixed in a weight ratio of material: ball: water = 1:2:0.4, and the mixture is added into a ball mill for ball milling. The fineness is controlled at 0.7-1.0% of the residue on the 10,000-hole sieve to obtain the glaze slurry for the base glaze.

[0058] Kaolin has good plasticity, which helps the bottom glaze layer 200 to form good adhesion and uniform coating on the ceramic body 100. In addition, the whiteness of kaolin helps to improve the aesthetics of ceramic products. At the same time, it can improve the suspension and stability of the glaze, so that the glaze is evenly distributed during the firing process to form a smooth and uniform glaze surface. High-temperature potassium sand is the main component for forming the glass phase. It has a wide melting range and a large high-temperature viscosity. It can broaden the melting and maturing temperature range of the glaze, which is conducive to porcelain formation and lowering the firing temperature, improving the gloss, transparency and smoothness of the glaze layer, and improving the chemical stability of the glaze layer. Quartz can combine with other oxides at high temperatures to form a stable glass phase structure, enhancing the hardness and wear resistance of the glaze surface; the addition of quartz can also improve the gloss and transparency of the glaze surface. Calcined talc can increase the wear resistance of glaze, fill minor defects, and improve the smoothness of glaze surface; it can also adjust the melting temperature of glaze, making it easier for glaze to melt at an appropriate temperature and form a uniform glaze layer, preventing glaze from cracking and peeling, and improving the stability and durability of glaze surface. The first frit can melt rapidly at high temperature, promote the melting and mixing of various components in glaze, form a uniform glass phase structure, and enhance the chemical corrosion resistance of glaze, and improve the service life of glaze.

[0059] The base glaze of the present invention does not need to use zirconium silicate, thereby solving the problem of high cost caused by using zirconium silicate base glaze.

[0060] In one embodiment of the present application, the chemical composition of the first frit, measured by mass percentage, includes:

[0061] SiO2 54.97%, Al2O3 11.21%, Fe2O3 0.12%, CaO 13.75%, MgO 0.45%, K2O2.44%, Na2O 1.37%, ZnO 2.17%, TiO2 13.52% 。

[0062] SiO2 in the embodiment of the present application, as the main chemical component, can react with other oxides at high temperature to form a stable glass phase structure, enhance the hardness and wear resistance of the glaze, help improve the suspension and stability of the glaze, and ensure that the glaze is evenly distributed during the firing process. Al2O3 combined with SiO2 can form mullite crystals, enhance the strength and stability of the glaze, and at the same time, Al2O3 can also affect the liquid phase viscosity, help resist high-temperature deformation, and ensure the stability of the glaze during high-temperature firing; CaO and MgO, as alkaline earth metal oxides, can reduce the firing temperature of the glaze, improve the mechanical strength and transparency of the glaze; they can also promote the melting and reaction of the glaze, making the glaze more uniform and smooth. K2O and Na2O, as alkali metal oxides, are important flux components in the glaze, which can promote the melting and reaction of the glaze. They can reduce the melting point of the glaze, so that the glaze can form a uniform glass phase structure at a lower temperature. ZnO can improve the gloss and whiteness of the glaze. TiO2 can improve the whiteness of the glaze, making the ceramic tile present a purer and brighter color, and can also act as a flux to promote the melting and reaction of the glaze. By controlling the content of Fe2O3, the color and tone of the glaze can be fine-tuned.

[0063] The chemical composition of the first frit in the embodiment of the present application has significant benefits in optimizing glaze performance, promoting glaze melting and reaction, and improving the quality of ceramic tiles. It can ensure that the glazed ceramic tiles form a uniform, smooth and decorative glaze during the firing process, while improving the durability and service life of the product.

[0064] In one embodiment of the present application, the chemical composition of the base glaze layer 200 includes, by mass percentage:

[0065] SiO2 70~74%, Al2O3 10~12%, Fe2O3 0.1~0.2%, CaO 5~6%, MgO 0.5~2%, K2O 1.5~2.5%, Na2O 1~2%, TiO2 5~6%, ZnO 0.5~1%.

[0066] The bottom glaze layer 200 of the embodiment of the present application contains titanium dioxide, which has a photocatalytic effect under light, which accelerates the decomposition of dirt and bacteria, degrades pollutants, and inhibits bacterial reproduction. The photocatalytic effect of titanium dioxide is used in many places in life for disinfection and deodorization, such as the paint used for decorating toilets and house walls, which contains titanium dioxide.

[0067] In one embodiment of the present application, the raw material formula of the glaze layer 300 includes, by mass percentage:

[0068] 20-30% albite, 8-12% calcite, 32-42% second melt, 8-12% quartz, 6-10% dolomite, 8-12% barium carbonate, 0.1-1% copper oxide, and 0-0.1% cobalt oxide.

[0069] Specifically, when preparing the glaze, the raw materials are mixed according to the above formula, 0.15% of sodium carboxymethyl cellulose (CMC), 0.3% of sodium tripolyphosphate, and 0.05% of preservatives are added to the total mass of the glaze, and the mixture is added into a ball mill in a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled to be 0.1-0.3% of the residue on the sieve of a 10,000-hole sieve to obtain a glaze slurry for the glaze.

[0070] The ratio of the glaze raw materials in the embodiment of the present application enables the glaze layer 300 to have suitable viscosity and surface tension, thereby producing an ideal glaze flow effect.

[0071] In one embodiment of the present application, the chemical composition of the second frit, measured by mass percentage, includes:

[0072] SiO2 52.37%, Al2O3 17.12%, Fe2O3 0.09%, CaO 11.42%, MgO 1.34%, K2O4.08%, Na2O 11.25%, BaO 1.96%, ZnO 0.37%.

[0073] Specifically, SiO2, Al2O3, CaO, MgO and other components in the frit can melt rapidly at high temperatures to form a stable glass phase structure; the presence of alkali metal oxides such as K2O and Na2O can further reduce the melting point and accelerate the melting process of the glaze;

[0074] The chemical composition of the second frit in the embodiment of the present application has significant benefits in optimizing glaze performance, promoting glaze melting and reaction, and improving the quality of ceramic tiles. It can ensure that the glazed ceramic tiles form a uniform, smooth and decorative glaze during the firing process, while improving the durability and service life of the product.

[0075] In one embodiment of the present application, the chemical composition of the glaze layer 300, measured by mass percentage, includes:

[0076] SiO2 50~56%, Al2O3 10~12%, Fe2O3 0.05~0.1%, CaO 12~16%, MgO2~3%, K2O 1~2%, Na2O 6~8%, BaO 9~11%, ZnO 0.1~0.2%, CuO 0.1~1%, CoO 0~0.1%.

[0077] Specifically, SiO2 as the main component, its high content helps to form a hard glaze, improves the wear resistance and scratch resistance of ceramic tiles; the addition of Al2O3 also enhances the hardness of the glaze, making it more durable; the appropriate content of CaO and MgO helps to improve the toughness of the glaze, preventing the glaze from easily cracking when subjected to external forces; the high content of SiO2 and Al2O3 makes the glaze have excellent corrosion resistance and can resist the erosion of various chemicals; the chemical composition in the glaze makes the glaze surface smooth and not easy to absorb dirt, easy to clean and maintain; the addition of CuO can inhibit the growth of bacteria to a certain extent; the addition of CuO and CoO provides a rich color change for the glaze, making the decorative effect of ceramic tiles more diverse; at the same time, these oxides can also affect the gloss of the glaze. K2O and Na2O as flux components can reduce the melting point of the glaze and promote the melting and reaction of the glaze.

[0078] The chemical composition of the surface glaze layer 300 of the present invention has significant benefits in optimizing physical properties, enhancing chemical stability, improving glaze decorative effects, and promoting glaze melting and reaction, which can ensure that the ceramic tiles form high-quality, highly decorative glazes during the firing process, while improving the durability and service life of the product.

[0079] In one embodiment of the present application, the chemical composition of the ceramic body 100, measured by mass percentage, includes:

[0080] SiO2 70~72%, Al2O3 18~20%, Fe2O3 1.5~2.5%, CaO 1~1.5%, MgO1.0~2.0%, K2O 2~3%, Na2O 1~2%, TiO2 0.5~1.0%, others 0.5~1.0%.

[0081] Specifically, SiO2 and Al2O3 are the main components in the ceramic body 100, and their high content helps to form a hard crystal structure, thereby improving the strength and hardness of the ceramic body 100. This makes the ceramic product more durable and able to withstand greater pressure and wear. By adjusting the ratio of SiO2, Al2O3 and other oxides (such as CaO, MgO), the thermal expansion coefficient of the ceramic body 100 can be optimized, thereby improving its thermal shock resistance, so that the ceramic product can maintain stable performance in an environment with large temperature changes. Appropriate K2O and Na2O content helps to lower the melting point of the ceramic body 100, making it easier to melt and shape during the firing process, and helps to improve the production efficiency and processing performance of the ceramic product. TiO2 and other oxides in the ceramic body 100 help to improve its antioxidant properties and prevent oxidation reactions from occurring at high temperatures and causing performance degradation. The presence of oxides such as Fe2O3 and TiO2 provides the ceramic body 100 with rich color changes. By adjusting the content and ratio of these oxides, ceramic products with unique colors can be customized.

[0082] The chemical composition of the ceramic body 100 of the embodiment of the present application optimizes the physical properties of the ceramic tile, enhances the chemical stability, and improves the color and gloss.

[0083] The present application also provides a method for preparing the glazed ceramic tile as described above, the method comprising:

[0084] Step S100, preparing ingredients according to a predetermined blank formula, and ball milling to obtain slurry;

[0085] Step S200, spray drying the slurry to obtain ceramic powder, and pressing the ceramic powder into a ceramic body;

[0086] Step S300: After the ceramic body is dried, a pre-prepared base glaze is applied on the dried ceramic body to obtain a base glaze layer, wherein the base glaze has a glaze amount of 400 to 600 g / m 2 ;

[0087] Step S400: Apply the pre-prepared top glaze on the base glaze layer to obtain a top glaze layer, wherein the amount of the top glaze applied is 700-1000 g / m 2 ;

[0088] Step S500: drying and firing the ceramic body with the base glaze and the top glaze to obtain a glazed ceramic tile.

[0089] Specifically, in step S100, the raw materials are wet-milled according to the blank formula and the weight ratio of material: ball: water = 1:1.2:0.4 to obtain mud. The water content of the mud is 30-35%, and the fineness of the mud is 2-2.5% on the 10,000-mesh sieve. In step S200, the mud passes through a spray drying tower and is spray-dried to obtain a ceramic powder. The ceramic powder has a water content of 5.5-6.5%, a bulk density ≥0.91, and a 40-mesh sieve residue of 48-58%. The ceramic powder is then pressed into a ceramic blank. In step S300, the ceramic blank is dried in a drying kiln, and a layer of base glaze is applied on the dried blank. The specific gravity is 1.77-1.79, the flow rate is 27-32 seconds, and the glaze amount is 400-600g / m 2 In step S400, the pre-prepared top glaze is applied on the base glaze layer, with a specific gravity of 1.80±0.01, a flow rate of 35 to 40 seconds, and a glaze amount of 700 to 1000 g / m 2 In step S500, the green body after applying the glaze slurry is dried by an infrared dryer and fired in a roller kiln at a firing temperature of 1180-1220°C for a firing period of 45-55 minutes. The green body is then edge-ground, packaged, and stored to obtain glazed ceramic tiles.

[0090] The amount of glazing applied to the bottom glaze in the embodiment of the present application is less than that of the top glaze. Since the viscosity of the top glaze layer is relatively low and the surface tension is also low, it has greater fluidity at high temperatures and is easy to form a flowing glaze. The amount of glazing applied to the top glaze is relatively large, so that the top glaze can form a more complex and rich flowing glaze texture, and the top glaze can be freely covered on the bottom glaze to form a unique macro-ordered and micro-disordered three-dimensional texture. The amount of glazing applied to the bottom glaze is relatively small. Since the main function of the bottom glaze layer is to adhere to the ceramic body and provide a flat and uniform base for the top glaze layer, the thinner bottom glaze layer can reduce the amount of glaze used and reduce costs without affecting its function as a base. A thicker top glaze layer can provide better wear resistance, corrosion resistance and pollution resistance, and protect the ceramic body from erosion by the external environment; at the same time, a thicker top glaze layer can also better show the flowing glaze effect and enhance the decorativeness of the ceramic tile.

[0091] The present invention can prepare ceramic tiles with three-dimensional textures and smooth glaze surfaces by adjusting the glaze formula. When stepping on the ceramic tiles barefoot or wearing socks, the acupuncture points on the soles of the feet can be pressed, which has a massage function. In addition, such ceramic tiles can be laid at the bottom of swimming pools and other places. This solves the problem that the three-dimensional decorative ceramic tiles are not strong enough in three-dimensional sense and the process is complicated. In addition, the base glaze of the present invention does not need to use zirconium silicate, thereby solving the problem of high cost of using zirconium silicate base glaze.

[0092] Specific embodiments are listed below for illustration.

[0093] Embodiment 1

[0094] Calculated by mass percentage, 10% kaolin, 26% high-temperature potassium sand, 24% quartz, 3% talc and 37% first frit are mixed, 0.1% CMC, 0.05% sodium tripolyphosphate, 0.2% sodium hexametaphosphate and 0.05% preservative of the total mass of the glaze are added, and the mixture is added into a ball mill at a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled at 0.7-1.0% of the residue on a 10,000-hole sieve to obtain a base glaze.

[0095] Calculated by mass percentage, 25% albite, 10% calcite, 35% second frit, 11% quartz, 8% dolomite, 10% barium carbonate, 0.98% copper oxide and 0.02% cobalt oxide are mixed, 0.15% CMC, 0.3% sodium tripolyphosphate and 0.05% preservative based on the total mass of the glaze are added, and the mixture is added into a ball mill at a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled at 0.1-0.3% of the residue on a 10,000-mesh sieve to obtain a surface glaze.

[0096] The preparation steps of ceramic tiles include:

[0097] Step A1, according to the raw material formula, the weight ratio is calculated as follows: material: ball: water = 1:1.2:0.4, and wet ball milling is performed to obtain a slurry with a moisture content of 30-35%, and a slurry fineness of 2-2.5% of the residue on a 10,000-mesh sieve. The slurry is spray dried in a spray drying tower to obtain a green body powder with a moisture content of 5.5-6.5%, a bulk density of ≥0.91, and a 40-mesh sieve residue controlled at 48-58%, and the green body is pressed into a green body;

[0098] Step A2, the green body is dried in a drying kiln;

[0099] Step A3, applying a layer of base glaze on the dried body, with a specific gravity of 1.78, a flow rate of 30 seconds, and a glaze amount of 575 g / m2;

[0100] Step A4, applying a layer of glaze, with a specific gravity of 1.81, a flow rate of 37 seconds, and a glaze amount of 826 g / m2;

[0101] Step A5, drying the green body with the glaze slurry applied by an infrared dryer;

[0102] Step A6, firing in a roller kiln, the firing temperature is 1201°C, and the firing cycle is 48 minutes;

[0103] Step A7: Packing and storage. The excellent rate is 95.9%.

[0104] Embodiment 2

[0105] Calculated by mass percentage, 8% kaolin, 27% high-temperature potassium sand, 21% quartz, 5% talc and 39% first frit are mixed, 0.1% CMC, 0.05% sodium tripolyphosphate, 0.2% sodium hexametaphosphate and 0.05% preservative of the total mass of the glaze are added, and the mixture is added into a ball mill at a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled at 0.7-1.0% of the residue on a 10,000-hole sieve to obtain a base glaze.

[0106] Calculated by mass percentage, 23% albite, 11% calcite, 41.7% second melt, 7% quartz, 8% dolomite, 9% barium carbonate, 0.2% copper oxide and 0.1% cobalt oxide are mixed, 0.15% CMC, 0.3% sodium tripolyphosphate and 0.05% preservative of the total mass of the glaze are added, and the mixture is added into a ball mill at a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled at 0.1-0.3% of the residue on a 10,000-mesh sieve to obtain a surface glaze.

[0107] The preparation steps of ceramic tiles include:

[0108] Step B1, according to the raw material formula, the weight ratio is calculated as follows: material: ball: water = 1:1.2:0.4, and wet ball milling is performed to obtain a slurry with a moisture content of 30-35% and a slurry fineness of 2-2.5% of the residue on a 10,000-mesh sieve. The slurry is spray dried in a spray drying tower to obtain a green body powder with a moisture content of 5.5-6.5%, a bulk density of ≥0.91, and a 40-mesh sieve residue controlled at 48-58%, and the green body is pressed into a green body;

[0109] Step B2, the green body is dried in a drying kiln;

[0110] Step B3, applying a layer of base glaze on the dried body, with a specific gravity of 1.79, a flow rate of 28 seconds, and a glaze amount of 431 g / m2;

[0111] Step B4, applying a layer of glaze, with a specific gravity of 1.80, a flow rate of 35 seconds, and a glaze amount of 790 g / m2;

[0112] Step B5, drying the green body with the glaze slurry applied by an infrared dryer;

[0113] Step B6, firing in a roller kiln, the firing temperature is 1190°C, and the firing cycle is 51 minutes;

[0114] Step B7: Packing and storage. The excellent rate is 96.8%.

[0115] Embodiment 3

[0116] Calculated by mass percentage, 12% kaolin, 25% high-temperature potassium sand, 26% quartz, 2% talc and 35% first frit are mixed, 0.1% CMC, 0.05% sodium tripolyphosphate, 0.2% sodium hexametaphosphate and 0.05% preservative of the total mass of the glaze are added, and the mixture is added into a ball mill at a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled at 0.7-1.0% of the residue on a 10,000-hole sieve to obtain a base glaze.

[0117] Calculated by mass percentage, 29% albite, 8% calcite, 37% second melt, 8% quartz, 6% dolomite, 11.5% barium carbonate, 0.47% copper oxide and 0.03% cobalt oxide are mixed, 0.15% CMC, 0.3% sodium tripolyphosphate and 0.05% preservative based on the total mass of the glaze are added, and the mixture is added into a ball mill at a weight ratio of material: ball: water = 1:2:0.4, and the mixture is milled, and the fineness is controlled at 0.1-0.3% of the residue on a 10,000-mesh sieve to obtain a surface glaze.

[0118] The preparation steps of ceramic tiles include:

[0119] Step C1, according to the raw material formula, the weight ratio is calculated as follows: material: ball: water = 1:1.2:0.4, and wet ball milling is performed to obtain a slurry with a moisture content of 30-35% and a slurry fineness of 2-2.5% of the residue on a 10,000-mesh sieve. The slurry is spray dried in a spray drying tower to obtain a green body powder with a moisture content of 5.5-6.5%, a bulk density of ≥0.91, and a 40-mesh sieve residue controlled at 48-58%, and the green body is pressed into a green body;

[0120] Step C2, the green body is dried in a drying kiln;

[0121] Step C3, applying a layer of base glaze on the dried body, with a specific gravity of 1.79, a flow rate of 31 seconds, and a glaze amount of 540 g / m2;

[0122] Step C4, applying a layer of glaze, with a specific gravity of 1.81, a flow rate of 39 seconds, and a glaze amount of 934 g / m2;

[0123] Step C5, drying the green body with the glaze slurry applied by an infrared dryer;

[0124] Step C6, firing in a roller kiln, the firing temperature is 1209°C, and the firing cycle is 45 minutes;

[0125] Step C7: Packing and storage. The excellent rate is 95.2%.

[0126] The present invention can achieve the following effects:

[0127] First, the ceramic tile of the present invention has undulating and crisscrossed surfaces, a strong three-dimensional effect, a smooth and delicate glaze, and a massage function.

[0128] Second, the ceramic tile glaze of the present invention has a strong sense of layering, simple color tone, and sparkling waves, which can achieve the visual effect of blue-green waves appearing when the breeze blows across the sea surface. Figure 2 and Figure 3 shown.

[0129] Third, the production process of the glazed ceramic tiles with massage function of the present invention is stable, simple, has a high quality rate, low cost, and can be mass-produced.

[0130] The present invention provides a glazed ceramic tile and a preparation method thereof, wherein the glazed ceramic tile comprises: a ceramic body, a bottom glaze layer arranged on the ceramic body, and a surface glaze layer arranged on the bottom glaze layer; the viscosity of the bottom glaze layer is greater than the viscosity of the surface glaze layer, and the surface tension of the bottom glaze layer is greater than the surface tension of the surface glaze layer. The surface glaze layer of the present invention has low viscosity and surface tension, and is easy to form a flowing glaze, and forms an uneven glaze surface after cooling, that is, the surface glaze layer produces a flowing glaze effect on the bottom glaze layer, forming a unique macroscopically ordered and microscopically disordered three-dimensional texture, which improves the decorative effect, and does not need to print a glue pattern, and does not have the problem of unclear pattern edges, and the process is simple.

[0131] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A glazed ceramic tile, characterized in that: The glazed ceramic tile comprises: a ceramic body, a bottom glaze layer arranged on the ceramic body, and a surface glaze layer arranged on the bottom glaze layer; the viscosity of the bottom glaze layer is greater than the viscosity of the surface glaze layer, and the surface tension of the bottom glaze layer is greater than the surface tension of the surface glaze layer.

2. The glazed ceramic tile according to claim 1, characterized in that: The bottom glaze layer is a titanium opacified glaze layer, and the top glaze layer is a glossy glaze layer.

3. The glazed ceramic tile according to claim 1, characterized in that: The raw material formula of the base glaze layer includes, by mass percentage: Kaolin 8-12%, high temperature potassium sand 22-30%, quartz 20-26%, calcined talc 1-5%, first frit 34-42%.

4. The glazed ceramic tile according to claim 3, characterized in that: The chemical composition of the first frit is calculated by mass percentage and includes: SiO2 54.97%、Al2O3 11.21%、Fe2O3 0.12%、CaO 13.75%、MgO 0.45%、K2O 2.44%、Na2O 1.37%、ZnO 2.17%、TiO2 13.52% 。 5. The glazed ceramic tile according to claim 1, characterized in that: The chemical composition of the base glaze layer, measured by mass percentage, includes: SiO2 70~74%, Al2O3 10~12%, Fe2O3 0.1~0.2%, CaO 5~6%, MgO 0.5~2%, K2O1.5~2.5%, Na2O 1~2%, TiO2 5~6%, ZnO 0.5~1%.

6. The glazed ceramic tile according to claim 1, characterized in that: The raw material formula of the glaze layer includes, by mass percentage: 20-30% albite, 8-12% calcite, 32-42% second melt, 8-12% quartz, 6-10% dolomite, 8-12% barium carbonate, 0.1-1% copper oxide, and 0-0.1% cobalt oxide.

7. The glazed ceramic tile according to claim 6, characterized in that: The chemical composition of the second frit is calculated by mass percentage and includes: SiO2 52.37%, Al2O3 17.12%, Fe2O3 0.09%, CaO 11.42%, MgO 1.34%, K2O 4.08%, Na2O 11.25%, BaO 1.96%, ZnO 0.37%.

8. The glazed ceramic tile according to claim 1, characterized in that: The chemical composition of the glaze layer, measured by mass percentage, includes: SiO2 50~56%, Al2O3 10~12%, Fe2O3 0.05~0.1%, CaO 12~16%, MgO2~3%, K2O 1~2%, Na2O 6~8%, BaO 9~11%, ZnO 0.1~0.2%, CuO 0.1~1%, CoO 0~0.1%.

9. The glazed ceramic tile according to claim 1, characterized in that: The chemical composition of the ceramic body, measured by mass percentage, includes: SiO2 70~72%, Al2O3 18~20%, Fe2O3 1.5~2.5%, CaO 1~1.5%, MgO1.0~2.0%, K2O 2~3%, Na2O 1~2%, TiO2 0.5~1.0%, others 0.5~1.0%.

10. A method for preparing a glazed ceramic tile according to any one of claims 1 to 9, characterized in that: The method comprises: The ingredients are prepared according to a predetermined blank formula, and ball-milled to obtain a slurry; The slurry is spray-dried to obtain ceramic powder, and the ceramic powder is pressed into a ceramic body; After the ceramic body is dried, a pre-prepared base glaze is applied on the dried ceramic body to obtain a base glaze layer, wherein the base glaze has a glazing amount of 400 to 600 g / m 2 ; Applying the pre-prepared top glaze on the base glaze layer to obtain a top glaze layer, wherein the amount of the top glaze applied is 700-1000 g / m 2 ; The ceramic body with the bottom glaze and the top glaze applied is dried and then fired to obtain a glazed ceramic tile.

Citation Information

Patent Citations

  • Ancient stone texture ceramic tile and preparation method thereof

    CN109320202A

  • Crystal flower dry granular glaze and locating crystal flower ceramic tile prepared through crystal flower dry granular glaze

    CN110759641A

  • Manufacturing method of environment-friendly daily-use underglaze spot transmutation glaze ceramic

    CN111018570A

  • Matt protective glaze with glossiness below 3 degrees for thin ceramic tile, thin ceramic tile and preparation method thereof

    CN111548016A

  • Double-layer flow difference reaction glaze and preparation method

    CN112645597A